2012
DOI: 10.1093/infdis/jis669
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Against TcdB, but Not TcdA, Prevents Development of Gastrointestinal and Systemic Clostridium difficile Disease

Abstract: These results highlight the importance of TcdB in the pathogenesis of CDI and the effectiveness of TcdB-specific antibody in treating CDI. However, the results raise new questions regarding the nature of TcdA interaction with therapeutic antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
96
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 24 publications
5
96
0
Order By: Relevance
“…10-12 Neutralization of both toxins appears to be necessary for maximal protection in rodents, but neutralization of toxin B alone appears to be sufficient in piglets. 13 In humans, the level of circulating antibodies against toxin A 14,15 or toxin B 16 has been correlated with protection against primary and recurrent C. difficile infection.A new approach to the prevention of recurrent C. difficile infection is the administration of monoclonal antibodies against C. difficile toxins (in addition to antibiotic therapy) as a form of passive immunity. Actoxumab (MK-3415/GS-CDA1/ CDA1) and bezlotoxumab (MK-6072/MDX-1388/ CDB1) are fully human monoclonal antibodies that bind and neutralize C. difficile toxins A and B, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10-12 Neutralization of both toxins appears to be necessary for maximal protection in rodents, but neutralization of toxin B alone appears to be sufficient in piglets. 13 In humans, the level of circulating antibodies against toxin A 14,15 or toxin B 16 has been correlated with protection against primary and recurrent C. difficile infection.A new approach to the prevention of recurrent C. difficile infection is the administration of monoclonal antibodies against C. difficile toxins (in addition to antibiotic therapy) as a form of passive immunity. Actoxumab (MK-3415/GS-CDA1/ CDA1) and bezlotoxumab (MK-6072/MDX-1388/ CDB1) are fully human monoclonal antibodies that bind and neutralize C. difficile toxins A and B, respectively.…”
mentioning
confidence: 99%
“…[10][11][12] Neutralization of both toxins appears to be necessary for maximal protection in rodents, but neutralization of toxin B alone appears to be sufficient in piglets. 13 In humans, the level of circulating antibodies against toxin A 14,15 or toxin B 16 has been correlated with protection against primary and recurrent C. difficile infection.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] We recently published a paper of our experimental results with human monoclonal antibodies used to investigate roles of TcdA and TcdB in the pathogenesis of CDI. 6 Interestingly, we found that only anti-TcdB was required in the piglet model to protect piglets from systemic and gastrointestinal lesions following oral inoculation with C. difficile, and that piglets treated with only anti-TcdA actually fared worse than untreated controls. This finding drew into question the long-standing hypothesis that TcdA was actually more important in the pathogenesis of disease, but was in agreement with other recent work highlighting the importance of TcdB.…”
Section: Introductionmentioning
confidence: 80%
“…6 Systemic administration of purified toxins allowed us to isolate each toxin from the other and revealed that both are quite potent and elicit severe systemic and gastrointestinal lesions, with each causing differential lesions. In contrast to the in vitro knowledge that TcdB is generally toxic to cells in much lower concentrations, we found the reality in vivo to be the opposite, with rTcdA causing equally severe disease at least a 50-fold lower dose where 2 μg of rTcdA was as toxic as 100 μg of rTcdB.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In humans, this supplementary infusion to primary antibiotics has shown remarkably lower recurrence rates. 10 Given these encouraging findings, a study was designed to clarify how these targeted serum antibodies access the colonic lumen.…”
mentioning
confidence: 99%